Visualization technologies for material development in professional training of future specialists - Alieksieieva, Ganna; Novak, Olga; Miziuk , Viktoriia; Saienko, Yuliia (Scientific notes of the pedagogical department, 2021)
The article presents the experience of using visualization technology in the professional training of future engineers-teachers of computer profile, in particular video lectures on the example of training IT specialists. It is emphasized that it is necessary to change the paradigm of teaching computer disciplines in the context of visualization of didactic materials as a basis for the abstraction of material. Practical aspects of the development of didactic and methodical materials of technology of students training for computer science’ school course with the video materials used are considered. It is proved that a large number of different methods and tools of teaching is an effective mechanism that can solve both educational and methodological problems for the modern educational innovations’ application in higher education, optimize the educational process and implement new approaches to lifelong learning. It is established that the use of e-learning systems with the implementation of visualization contributes to a more successful perception and memorization of educational material. This is due to the work intensification at the same time both hemispheres: the left hemisphere usually works in traditional learning, the right hemisphere, the responsibility for the image-emotional perception of the proposed information, is activated by visualization. As a result, there is a creative and professional development of personality. The classical methods of teaching the discipline "School course of informatics" with lecture-practical forms of teaching with text didactic materials that have a low level of abstraction compared to the use of video materials are analysed. It is proved that, due to the technical advantages of the use of video materials, the quality and efficiency of the educational process is improved. That is, visualization technologies have significant potential, which guarantees high-quality professional training of students.